Genetic Adaptation of a Mevalonate Pathway Deficient Mutant in Staphylococcus aureus - Reichert, Sebastian; Ebner, Patrick; Bonetti, Eve-Julie; Luqman, Arif; Nega, Mulugeta; Schrenzel, Jacques; Spröer, Cathrin; Bunk, Boyke; Overmann, Jörg; Sass, Peter; François, Patrice; Götz, Friedrich (Frontiers in Microbiology, 2018)
In this study we addressed the question how a mevalonate-auxotrophic Staphylococcus aureus ΔmvaS mutant can revert to prototrophy. This mutant couldn't grow in the absence of mevalonate. However, after a long lag-phase of four to six days the mutant adapted from auxotrophic to prototrophic phenotype. During that time, it acquired two point mutations: One mutation in the coding region of the regulator gene spx, which resulted in an amino acid exchange that decreased Spx function. The other mutation in the upstream-element within the core-promoter of the mevalonate lactonase gene drp35. This mutation led to an increased expression of drp35. In repeated experiments the mutations always occurred in spx and drp35 and in the same order. The first detectable mutation appeared in spx and allowed slight growth; the second mutation, in drp35, increased growth further. Phenotypical characterizations of the mutant showed that small amounts of the lipid-carrier Undecaprenol are synthesized, despite the lack of mvaS. The growth of the adapted clone, ΔmvaSad, indicates that the mutations reawake a rescue bypass. We think that this bypass enters the mevalonate pathway at the stage of mevalonate, because blocking the pathway downstream of mevalonate led to growth arrest of the mutant. In addition, the lactonase Drp35 is able to convert mevalonolactone to mevalonate. Summarized, we describe here a mutation-based two-step adaptation process that allows resuscitation of growth of the ΔmvaS mutant.